From secretory otitis to retraction cholesteatoma - D. M. Kokorkin; V. V. Skorobogaty; O. O. Gusakova; P. P. Shevlyuk; N. A. Kolyada (Сучасні медичні технології)
Based on the preliminary examination and further treatment of 980 children, the most influential consequences of secretory otitis were identified and the means of their prevention were proposed. Based on the results of long-term observation, conclusions were drawn. Chronic secretory otitis develops in 16% of children with recurrent secretory otitis, in 25% of cases the disease becomes malignant, and in 10% of cases goes into the stage of chronic purulent otitis media. In the treatment of recurrent and complicated chronic secretory otitis, it is advisable to follow the sequence of treatment, because 68% of children show existing or hidden signs of sinusitis, which requires prior surgical treatment. Among the detected forms, polyposis sinusitis with deformation of the nasal septum predominates (88,5%).